Benefit of Anticoagulation Therapy in Hyperthyroidism‐Related Atrial Fibrillation. Issue 8 (6th August 2015) - Chan, Pak‐Hei; Hai, Jojo; Yeung, Chun‐Yip; Lip, Gregory Y.H.; Lam, Karen Siu‐Ling; Tse, Hung‐Fat; Siu, Chung‐Wah
ABSTRACT Background Existing data on the risk of ischemic stroke in hyperthyroidism‐related atrial fibrillation (AF) and the impact of long‐term anticoagulation in these patients, particularly those with self‐limiting AF, remain inconclusive. Hypothesis Risk of stroke in hyperthyroidism‐related AF is the same as nonhyperthyroid counterparts. Methods This was a single‐center observational study of 9727 Chinese patients with nonvalvular AF from July 1997 to December 2011. Patients with AF diagnosed concomitantly with hyperthyroidism were identified. Primary and secondary endpoints were defined as hospitalization with ischemic stroke and intracranial hemorrhage in the first 2 years. Patient characteristics, duration of AF, and choice of antithrombotic therapy were recorded. Self‐limiting AF was defined as <7 days' duration. Results Out of 9727 patients, 642 (6.6%) had concomitant hyperthyroidism and AF at diagnosis. For stroke prevention, 136 and 243 patients (21.1% and 37.9%) were prescribed warfarin and aspirin, respectively, whereas the remaining patients (41.0%) received no therapy. Ischemic stroke occurred in 50 patients (7.8%), and no patient developed hemorrhagic stroke. Patients with CHA2DS2‐VASc of 0 did not develop stroke. Warfarin effectively reduced the incidence of stroke compared with aspirin or no therapy in patients with CHA2DS2‐VASc ≥1 and non–self‐limiting AF, but not in those with self‐limiting AF or CHA2DS2‐VASc of 0. Presence of hyperthyroidism did not confer additional risk of ischemic stroke compared with nonhyperthyroid AF. Conclusions Patients with hyperthyroidism‐related AF are at high risk of stroke (3.9% per year). Warfarin confers stroke prevention in patients with CHA2DS2‐VASc ≥1 and non–self‐limiting AF. Overall stroke risk was lower in hyperthyroid non–self‐limiting AF patients compared with nonhyperthyroid counterparts.